(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the casting of aluminum alloy 6061 using green sand molds to evaluate the heat transfer coefficient (HTC) and solidification behaviour for different cast shapes. The shapes employed for the study includes rectangular plate, square bar and cylindrical bar. Aluminum alloy 6061 ingots were melted and poured at 700°C into the moulds of rectangular plate, square bar, and cylindrical bar configurations. Experimental results revealed that the HTC varies across different shapes, with the rectangular plate exhibiting the highest average HTC of 131.6 W/m²K, followed by the cylindrical bar (98 W/m²K) and square bar (73.7 W/m²K). The study demonstrated that shapes with lower casting modulus exhibit faster solidification due to enhanced heat dissipation. The casting of shapes that involves using aluminium alloy 6061 solidified within 105 seconds after pouring of the molten metal into mould cavity and also plate was the first to solidify. The thermal conductivity of the alloy was consistent with ASTM standards, confirming the material's suitability for casting applications. The experimental result shows that thermal conductivity of the alloy was 102.3 WmK and the value was within range of stated value (85 - 173 W/mK) by ASTM. Heat transfer coefficient (HTC) in the cast objects was 101.1 W/m2K. These findings highlight the influence of casting geometry on heat transfer and solidification characteristics, providing valuable insights for optimizing casting processes.